Metabolic Syndrome and Selective Inflammatory Markers in Psoriatic Patients - Vachatova, Simona; Andrýs, Ctirad; Krejsek, Jan; Salavec, Miloslav; Ettler, Karel; Rehacek, Vit; Cermakova, Eva; Malkova, Andrea; Fiala, Zdenek; Borska, Lenka (Journal of immunology research, 2016)
The presented article studies the role of selected inflammatory and anti-inflammatory serum markers of psoriatic patients in the pathogenesis of metabolic syndrome (MS) and psoriasis. The study is based on the comparison between the group of psoriatic patients (74) and the control group (65). We found significantly higher BMI (p < 0.05) and diastolic blood pressure (p < 0.05) in the psoriatic patients. The values of waist circumference and BMI were significantly higher (p < 0.05) in the male patients compared to the men in the control group. The analysis revealed significantly higher CRP (p < 0.001), Lp-PLA2 (p < 0.001), leptin (p < 0.01), and resistin (p < 0.01) levels in the psoriatic patients. Significantly higher levels of CRP (p < 0.01), Lp-PLA2 (p < 0.001), leptin (p < 0.01), and resistin (p < 0.05) were found in the patients with MS compared to the controls with MS. The level of adiponectin was significantly lower (p < 0.01) in the patients with MS. Finally, we found significantly higher level of Lp-PLA2 (p < 0.001) in the group of patients without MS compared to the controls without MS. In conclusion, observed inflammatory and anti-inflammatory markers (CRP, adiponectin, leptin, resistin, and Lp-PLA2) are involved in both pathogenesis of MS and pathogenesis of psoriasis. The level of Lp-PLA2 indicates the presence of subclinical atherosclerosis (cardiovascular risk) in psoriatic patients.
Keywords: Resistin; dospělí; Female; psoriáza; adiponektin; biologické markery; C-Reactive Protein; Biomarkers; Adult; ženské pohlaví; mladý dospělý; obvod pasu; Adolescent; Leptin; Metabolic Syndrome; Adiponectin; lidé; studie případů a kontrol; metabolický syndrom; Aged, 80 and over; 1-Alkyl-2-acetylglycerophosphocholine Esterase; krevní tlak; Waist Circumference; leptin; Male; Case-Control Studies; Aged; 1-alkyl-2-acetylglycerofosfocholinesterasa; Young Adult; index tělesné hmotnosti; resistin; lidé středního věku; C-reaktivní protein; senioři nad 80 let; senioři; mužské pohlaví; Blood Pressure; Body Mass Index; Psoriasis; Middle Aged; mladiství; Humans